Analysis of Financial Performance for Rice Producing Companies Listed on the IDX to the Volatility Increase in Rice Prices - Bara Borneo (Jurnal Riset dan Inovasi Manajemen, 2024)
The volatility increase in rice prices has already started since August 2022 where this condition continues until 2023. This increase in rice prices brought a negative sentiments to rice producing companies such as HOKI and NASI in their Net Profit Margin. Therefore this research focuses to provide insights for investors and companies on the impact of volatilities increase in rice prices to financial performances of rice producing companies that listed in IDX. By using quantitative research methods and analyzing various financial ratios, the research investigates how rising rice prices affect the profitability, efficiency, and market performance of these companies. The results indicate that the volatility in rice prices negatively impacted the financial performance of rice-producing companies listed on the IDX in terms of profitability. However, it had a mixed impact on marketability and efficiency with the data showing positive differences. Benchmarking with companies from other countries also suggests areas for improvement for the companies studied.